Isolation and partial characterization of a 30 kDa adhesin from Paracoccidioides brasiliensis - Andreotti, P. F.; da Silva, JLM; Bailao, A. M. B.; Soares, C. M. A.; Benard, G.; Soares, Christiane Pienna [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (Elsevier B.V., 2005)
The virulence of Paracoccidioides brasiliensis can be attenuated or lost after long periods of repeated subculturing and reestablished after animal inoculation. Only one adhesin (gp43) has been described until now, among the various identified components of P. brasiliensis, and gp43 shows adhesion to laminin. Thus, the present study was designed to isolate and characterize factors putatively related to the capacity of this fungus to adhere to the host by comparing P brasiliensis samples, taken before and after animal inoculation. The two samples differed in their pattern of adhesion and invasion. The sample recently isolated from animals (Pb18b) demonstrated a greater capacity to adhere and to invade the Vero cells than the one subcultured in vitro (Pb18a). Extract from Ph18b also showed higher levels of protein expression than that from Pb18a, when two-dimensional electrophoresis gels were compared. A protein species of 30 kDa, pI 4.9, was more evident in the Pb18b extract and had properties of adhesin. Laminin, but none of the other extracellular matrix (ECM) components, such as fibronectin, collagen I and IV, bound specifically to the P. brasiliensis 30 kDa protein. The roles of 30 kDa and gp43 in cellular interactions were investigated and the adhesion of P. brasiliensis yeast cells was intensively inhibited by pre-treatment of epithelial cells with 30 kDa protein and gp43. Thus, this study presents evidence that adhesion capacity could be related to virulence, and that a 30 kDa adhesin accumulated differentially in samples with different levels of pathogenicity. This protein and its adhesion characteristics are being published for the first time and may be related to the virulence of P brasiliensis. (c) 2005 Elsevier SAS. All rights reserved.
Keywords: Paracoccidioides brasiliensis; adhesin; 30 kDa protein; laminin